Stomatin interacts with GLUT1/SLC2A1, band 3/SLC4A1, and aquaporin-1 in human erythrocyte membrane domains - Rungaldier, Stefanie (Elsevier Pub. Co, 2013)
The widely expressed, homo-oligomeric, lipid raft-associated, monotopic integral membrane protein stomatin and its homologues are known to interact with and modulate various ion channels and transporters. Stomatin is a major protein of the human erythrocyte membrane, where it associates with and modifies the glucose transporter GLUT1; however, previous attempts to purify hetero-oligomeric stomatin complexes for biochemical analysis have failed. Because lateral interactions of membrane proteins may be short-lived and unstable, we have used in situ chemical cross-linking of erythrocyte membranes to fix the stomatin complexes for subsequent purification by immunoaffinity chromatography. To further enrich stomatin, we prepared detergent-resistant membranes either before or after cross-linking. Mass spectrometry of the isolated, high molecular, cross-linked stomatin complexes revealed the major interaction partners as glucose transporter-1 (GLUT1), anion exchanger (band 3), and water channel (aquaporin-1). Moreover, ferroportin-1 (SLC40A1), urea transporter-1 (SLC14A1), nucleoside transporter (SLC29A1), the calcium-pump (Ca-ATPase-4), CD47, and flotillins were identified as stomatin-interacting proteins. These findings are in line with the hypothesis that stomatin plays a role as membrane-bound scaffolding protein modulating transport proteins.